Identification of bacteriocin-producing bacteria from shrimp paste using 16S rRNA gene method and assay for MIC of their bacteriocin - SUKMAWATI SUKMAWATI; METUSALACH METUSALACH; SYAHRUL SYAHRUL (Society for Indonesian Biodiversity, 2025)
Abstract. Sukmawati S, Metusalach M, Syahrul S. 2025. Identification of bacteriocin-producing bacteria from shrimp paste using 16S rRNA gene method and assay for MIC of their bacteriocin. Biodiversitas 26: 3367-3377. Bacteria play a crucial role in various ecosystems, serving as key components in biogeochemical cycles and sources of bioactive compounds. Bacteriocins, a type of secondary metabolite, are antimicrobial compounds produced by bacteria to inhibit the growth of other microorganisms, notable for their specificity, stability, and eco-friendliness. These compounds have significant potential in various applications, ranging from food preservation to medical use as an alternative to antibiotics. This study aims to identify bacteriocin-producing bacteria isolated from shrimp (Acetes) paste (terasi) and evaluate the Minimum Inhibitory Concentration (MIC) of their crude bacteriocin for its antimicrobial potential. A descriptive method was employed to characterize the bacterial species producing crude bacteriocin from shrimp paste and assess the MIC ability of potential bacteria in inhibiting indicator bacteria. The results revealed that bacteriocin-producing bacteria isolated from shrimp paste, with sample codes TRS1, TRS2, and TRS3 were identified as Bacillus tropicus strain MCCC 1A01406, Bacillus nitratireducens strain MCCC 1A00732, and Bacillus paramycoides strain MCCC 1A04098, respectively. These three bacterial isolates could produce bacteriocins. The results of the Minimum Inhibitory Concentration (MIC) test showed that at the lowest bacteriocin concentration, but with the highest minimum inhibition, sample TRS1 had an inhibition value of 2.3 mm at a concentration of 0.19%, sample TRS3 had an inhibition value of 1.0 mm at a concentration of 0.19%, and sample TRS2 had an inhibition value of 1.2 mm at a concentration of 0.78%. A total of three isolates identified as Bacillus spp. demonstrated antimicrobial activity with MIC values ranging from 0.19% to 0.78%.